Comprehensive Assessment of the Energy Performance Indicator of a Gold Mining Industry in Indonesia - Mahandari, Cokorda Prapti; Yamin, Mohamad; Palaloi, Sudirman; Hasan, Muhammad Syukri; Kurniawan, Cucuk (Science and Technology: Developments and Applications Vol. 10, 2025)
The gold mining industry encounters a growing pressure to reduce its energy consumption cum environmental impact. In recent years, many mining companies have programs to reduce their specific energy requirements in ore processing, in that way improving their competitiveness. Energy Performance Indicators for gold mining represent energy consumption, energy intensity or Specific Energy Consumption (SEC). Energy Audit follows ISO 50002 standards had been done on one of the gold mining industries in North Maluku, Indonesia that has operations involving two underground mining. As part of the energy audit report, this paper presents energy sources and energy consumption, specific energy consumption cum energy intensity of the plant. Energy audit methods include energy audit planning, opening meetings, data collection, measurement plant, site visit, data analysis, energy audit reporting and closing audit. Most electricity data were collected from the SCADA system which the company use to monitor and control maximum electricity demand. Secondary data were collected from the areas of power generating facility, underground mining, mill production, Dry Stack Tailing (DST) plant and Supporting facility area. Arithmetic mean, energy intensity equation and visual graphic methods were employed to investigate the energy profile and energy performance indicator of this gold mining. As the site is located far away from the national grid then four Diesel powerhouses generate the electricity. Fuel consumption for four units mainly electricity generation, transportation, heavy-duty and supporting are investigated thoroughly. Since Diesel powerhouse occupy more than 80% fuel consumption then the Diesel power houses is the Significant energy users (SEU). Further study of SEC and on heat rate of the powerhouse is carried out and benchmarked with the IEA. It shows that the powerhouses have excellent performance as SEC and the heat rate is lower than typical powerhouses. Fuel consumption of PT Nusa Halmahera Minerals, especially for power plants, is the largest. The highest energy consumption occurred in 2022, primarily due to facility modifications shifting from a full Merrill-Crowe (MCR) process to a combined MCR and Carbon-in-Leach (CIL) process. The powerhouse distributed electricity to four different units, Kencana Underground Mining, Toguraci Underground Mining, Mill and Merril Crowe Processes and Supporting Unit. Among these units, Togurachi underground mining with its uniqueness became the highest electricity end user as expected. It covers more than 40% of electricity consumption resulting in quite high total energy intensity by ore milled which is approximately 475 kWh/ton (1710 MJ/ton) and energy intensity by Dore bullion is 1,420 kWh/ounce (5108 MJ/oz). As part of the energy audit report, the result of this paper is beneficial for preparing documents on energy management systems, environmental management systems, quality management systems and LCA. Many significant opportunities identified in the energy audit report for reducing mining’s energy consumption include optimization, big data and artificial intelligence.